He said, she said’: assessing dyadic agreement of reported sexual behaviour and decision-making among an HIV sero-discordant couples cohort in Uganda - Birungi, Josephine; Maldoon, Cathrine; Kanters, Steve; King, Racheal; Nyonyintono, Moreen; Khanakwa, Sarah; Moore, David. M. (BMJ, 2016)
Background The intimate nature of sexuality makes it challenging to accurately measure sexual behaviour. To assess response reliability, we examined agreement between couples in heterosexual HIV sero-discordant partnership on survey questions regarding condom use and sexual decision-making. Methods Data for this analysis come from baseline data from a cohort study of HIV sero- discordant couples in Jinja, Uganda. We examined the degree of agreement between male and female partners on standard measures of sexual behaviour using the kappa (κ) statistic and 95% confidence intervals (95% CIs). Results Among 409 couples, the median age for the male partner was 41 [interquartile range (IQR) 35–48] years and the female partner was 35 (IQR 30–40) years. Among 58.2% of the couples, the male was the HIV-positive partner. Questions with high or substantial couple agreement included condom use at last sex (κ=0.635, 95% CI 0.551–0.718) and frequency of condom use (κ=0.625, 95% CI 0.551–0.698). Questions with low or fair couple agreement included decision-making regarding condom use (κ=0.385, 95% CI 0.319–0.451), wanting more biological children (κ=0.375, 95% CI 0.301– 0.449) and deciding when to have sex (κ=0.236, 95% CI 0.167–0.306). Conclusions Survey questions assessing condom use had the highest level of couple agreement and questions regarding sexual decision-making and fertility desire had low couple agreement. Questions with high agreement have increased reliability and reduced measurement bias; however, questions with low agreement between couples identify important areas for further investigation, particularly perceived relationship control and gender differences.
Keywords: Sexual behaviour; Sero-discordant couples; HIV